Nilai Hidup Rukun Pondasi Kebhinekaan Dalam Mengantasipasi Radikalisme - I Nyoman Warta; I Nyoman Santiawan; I Nyoman Suendi (Lembaga Penerbit Sekolah Tinggi Hindu Dharma Klaten, 2019)
The Importance of Tat Twam Asi Values ​​upholds humanistic values ​​with a strong religious spirit and sense, a sense of universal brotherhood that is not limited by religion, science and behavior which is limited by awidhya or darkness of mind, words and deeds. Explaining, hurting other people is essentially hurting themselves. Actually living in harmony indicates respect for others in essence of respecting oneself, and vice versa against others in essence against one's own self, in other words Tat Twam Asi is upholding the human values ​​that have been created by Ida Sang Hyang Widhi / God Almighty One as a necessity and need for the realization of a peaceful, harmonious and anhamham harmony as a tangible manifestation of a pluralistic state. What's more we see the teachings of ahimsa karma which are universal Vedic teachings, the value of ahimsa is popularized by Gandhi, who strongly emphasizes, must not kill, hurt, slander, envy, and pitting sheep of various lies as rhetoric wrapped in religious teachings, in fact it is not justified by the teachings of Hinduism. Because, in essence, it hurts life in this universe, its thighs actually hurt themselves. Because Hinduism places great importance on universal truths, everything that exists has the same rights and obligations and cannot be bound by others in any form or way. If the values ​​of harmony, religious norms in the archipelago are tainted, morality is degraded, then destruction, evil will be rampant. Sadistic murders occur everywhere, raping, drug networks, coronations as if they are difficult to eradicate and terrorism networks that are enemies of the world and humanity have not been able to be overcome to the maximum. Sophisticated communication networks often inconvenience humanity. This goes back to the true human identity, by grounding religious teachings, understood to be lived and practiced in the life of the nation and state, religious teachings are not solely in the air, but religious values ​​are able to interpret this life in accordance with the goals of human life namely Catur Marga Yoga. Then life will be wise gem rifah tablets jinawi.